2012
DOI: 10.1128/jcm.01384-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the GenMark Diagnostics eSensor Respiratory Viral Panel to Real-Time PCR for Detection of Respiratory Viruses in Children

Abstract: A novel eSensor respiratory viral panel (eSensor RVP) multiplexed nucleic acid amplification test (GenMark Diagnostics, Inc., Carlsbad, CA) was compared to laboratory-developed real-time PCR assays for the detection of various respiratory viruses. A total of 250 frozen archived pediatric respiratory specimens previously characterized as either negative or positive for one or more viruses by real-time PCR were examined using the eSensor RVP. Overall agreement between the eSensor RVP and corresponding real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 36 publications
6
80
0
Order By: Relevance
“…Of importance was the RNase P internal control of the LDA, which gave a positive signal for all the samples tested, while the internal control of the Simplexa Flu A/B & RSV kit failed in 4 patient samples (2.3%) that were negative for influenza viruses and RSV. The Simplexa Flu A/B & RSV kit failure rate was higher than the 1.5% reported for other fully automated assays, such as the eSensor respiratory viral panel (12). Upon stratifying the patient samples by virus type, the LDA detected 30 influenza A viruses, whereas the Simplexa Flu A/B & RSV kit detected 28.…”
mentioning
confidence: 67%
“…Of importance was the RNase P internal control of the LDA, which gave a positive signal for all the samples tested, while the internal control of the Simplexa Flu A/B & RSV kit failed in 4 patient samples (2.3%) that were negative for influenza viruses and RSV. The Simplexa Flu A/B & RSV kit failure rate was higher than the 1.5% reported for other fully automated assays, such as the eSensor respiratory viral panel (12). Upon stratifying the patient samples by virus type, the LDA detected 30 influenza A viruses, whereas the Simplexa Flu A/B & RSV kit detected 28.…”
mentioning
confidence: 67%
“…These findings suggest that the discordant results were frequently reported in samples containing low viral copy. Other studies also indicated that discrepant results between RV assay was quite associated with sample's viral load 7, 8, 19, 20, 21. One samples by AP and three samples by AD identified as INF A positive by additional testing.…”
Section: Discussionmentioning
confidence: 97%
“…Performance evaluation studies for newly developed multiplex RV kits are weak, do not establish the reference standard method and therefore do not sufficiently calculate sensitivity and specificity of each test. Instead, some studies have suggested the reference test with in‐house multiplex real‐time PCR or commercial duplex PCR tests 5, 6, 7, 8. We performed a direct comparison of three commercial multiplex assays and produced the values of the agreement and kappa instead of sensitivity and specificity with the reference tests.…”
Section: Introductionmentioning
confidence: 99%
“…This announcement reflects the current move towards the development and commercialization of detection technologies for the diagnosis of infectious syndromes whether, enteric [1][2][3][4][5][6], respiratory [7][8][9][10][11][12][13], sexually transmitted [14], affecting the central nervous system [15] or causing sepsis [16,17]. Commercially available tests for the detection of specific pathogens associated with urinary tract infection, neonatal infection or infection in the immunocompromised host have also been developed by commercial diagnostic companies including Fast-track Diagnostics (Junglinster, Luxembourg), AusDiagnostics Pty Ltd (Sydney, Australia) and Seegene (Seoul, Korea).…”
Section: Introductionmentioning
confidence: 97%